Wind effects on symmetrical multiple core wall system of high-rise building - Samsudin, Hazwani (2014)
High-rise building is one of the phenomena that is inevitable. World has seen high-rise building as a solution to maximize the use of land. High-rise building is strongly related to response of the structure due to the wind. The development of high rise building has pushesd the limit of engineering to come out with better structural systems to reduce the wind-induced responses. Core wall system is said to be the most effective systems that can be implemented to reduce the wind effects on the structures. However, the greater the size of core wall used in the building, the lesser the usable space in the building. This paper is proposing the use of multiple core walls that are located at each corner of the building to maximize the use of space in the building as well as to study the effects of multiple core walls in reducing wind response on structures. A static analysis was performed by using ETABS to obtain the displacement and maximum stress of the building. The result of the studies shows that by implementing multiples core walls system, the along wind displacement can be reduced up to 94%, 89% and 87% for 10 storey building, 20 storey building and 30 storey building respectively. Both single central core wall system and multiple corner core wall system can be used to reduce the wind effect to the building where the single central core wall is more effective in reducing the displacement but, is less effective in reducing the stresses, compared to the results obtained from the analysis of multiple corner core wall system.